Análisis Crítico de la Normativa Constitucional en la Vulneración de Derechos en la Flora y Fauna en Galápagos - Torres Jaramillo, Emily Jazmín (2024)
The objective of this curricular integration work was to determine if the state intervenes effectively in the violation of flora and fauna in Galapagos, when the National Park and the Marine Reserve are being unprotected, in what way does the constitutional state intervene. Is there a constitutional analysis of the violation of flora and fauna in Galapagos? In response to this question, a constitutional analysis of the constitutional regulations and their application in the violation of the same was subjectively proposed. In order to achieve the proposed objectives, the methodology used was based on the empirical, descriptive method and, in addition, the application of the mixed approach, also linking descriptive and cross-sectional research. Theoretical and documentary techniques, interviews and surveys were also introduced, which were beneficial for ascertaining the diverse criteria of the actors involved in the process of the violation of flora and fauna in the Galapagos Archipelago. Based on the results, relevant information was obtained on the research topic, showing that there really is a violation within the biodiverse ecosystems of the island region, reaching the conclusion that there should be a reform to the law of penalties in Article 247 of the COIP and safeguard the constitutional principle of proportionality, The conclusion is that there should be a reform to the law of penalties in article 247 of the COIP and safeguard the constitutional principle of proportionality, so that there is equity as it is really stipulated in the laws that govern the legal system of a State, alluding to where the punishable regulations are effective to typify the illegal acts in the consular region, reducing the criminal burden in the current judicial system.